Ethics in times of Corona: Ordonomic reflections on (dys-)functional morality - Ingo Pies (Martin-Luther-Universität Halle-Wittenberg, Lehrstuhl für Wirtschaftsethik, 2020)
Dieser Artikel diente als Textgrundlage für eine 'Keynote Address', die ich am 26. Juni 2020 als Video-Vortrag zum IAMO Forum 2020 beigesteuert habe. Sie geht der Frage nach, inwiefern moralische Gefühle und helfen bzw. daran hindern, vernünftige Strategien zu finden, mit denen sich die Corona-Krise bewältigen lässt. Der Text formuliert Thesen zur Funktionalität und Dysfunktionalität individueller sowie kollektiver Moral und gibt eine Anregungen für eine kluge Weltinnenpolitik zum Risikomanagement globaler Herausforderungen. – – This article contains the text for a keynote address, delivered as a video presentation, for the IAMO Forum 2020. It discusses whether our moral sentiments help or impede finding reasonable strategies to cope with the Corona crisis. The text formulates hypotheses about the functionality and dysfunctionality of both individual and collective morality. Furthermore, it provides some suggestions for a prudent world-domestic institutionalization of risk-management to counter global challenges.
urn:nbn:de:gbv:3:2-123109
Keywords: 330; ethics; ordonomics; moral sentiments; pandemic; global public good; world-domestic politics; Ethik; Ordonomik; moralische Emotionen; Pandemie; Globales Öffentliches Gut; Weltinnenpolitik